2015
DOI: 10.1074/jbc.m115.661777
|View full text |Cite
|
Sign up to set email alerts
|

SET7/9 Enzyme Regulates Cytokine-induced Expression of Inducible Nitric-oxide Synthase through Methylation of Lysine 4 at Histone 3 in the Islet β Cell

Abstract: Background: SET7/9 regulates expression of NF-B target genes in non-␤ cells. Results: SET7/9 knockdown attenuated cytokine-induced expression of inducible nitric-oxide synthase and apoptosis in ␤ cells. Conclusion: SET7/9 regulates Nos2 expression through methylation of H3K4 in ␤ cells. Significance: SET7/9 contributes to proinflammatory cytokine signaling in the pancreatic ␤ cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Li et al [30] have shown that histone methyltransferase SET7/9 contributes to TNFa-induced transcription of MCP-1 by promoting sitespecific histone H3K4 trimethylation in macrophages, similar to what we have shown for ASH2. This observation has been further corroborated by Fujimaki et al [31] who showed that SET7/9 regulates TNF-ainduced transactivation of iNOS, another NF-jB target, in islet b cells. Various studies have also placed MLL4 [32] or MLL1 [33] at the center of proinflammatory transcription in macrophages.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Li et al [30] have shown that histone methyltransferase SET7/9 contributes to TNFa-induced transcription of MCP-1 by promoting sitespecific histone H3K4 trimethylation in macrophages, similar to what we have shown for ASH2. This observation has been further corroborated by Fujimaki et al [31] who showed that SET7/9 regulates TNF-ainduced transactivation of iNOS, another NF-jB target, in islet b cells. Various studies have also placed MLL4 [32] or MLL1 [33] at the center of proinflammatory transcription in macrophages.…”
Section: Discussionsupporting
confidence: 68%
“…This observation has been further corroborated by Fujimaki et al . who showed that SET7/9 regulates TNF‐α‐induced transactivation of iNOS, another NF‐κB target, in islet β cells. Various studies have also placed MLL4 or MLL1 at the center of proinflammatory transcription in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…As monomethylation at histone 3 lysine 4 by SET7/9 is generally associated with transcriptional activation 23,24 , we first focused our attention on the functional significance of SET7/9. The genome-wide transcriptional targets of SET7/9 were analyzed by chromatin immunoprecipitation-based deep sequencing (ChIP-seq) in MCF-7 cells.…”
Section: Identification Of Genome-wide Transcription Targets For Set7/9mentioning
confidence: 99%
“…Although, this did significantly reduce IFNγ, Il-1β, and TNFα-induced expression of Ccl2 , Ccl20 , Cxcl10 , Cxcl9 , and Il-15 , these reductions were relatively modest (1.8 to 3.6 fold). This suggests that the level of Wdr5 suppression achieved (only ~50% at the protein level) was not sufficient to completely block TrxG complex activity, or that other H3K4 methyltransferases independent of the TrxG complex, such as Setd7 [ 66 , 67 ], are involved. As an alternative approach we chose to use the small molecule inhibitor GSK-J4, which is converted intracellularly into GSK-J1, a potent inhibitor of Jmjd3 and Utx [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%